Taoism - Oldstone-Moore, Jennifer
Existing in China alongside Confucianism and Buddhism throughout the centuries, Taoism has had a major impact on Chinese intellectual and spiritual life. This concise guide offers an engaging introduction to the precepts, history and practices of Taoism, in a well-designed and attractively illustrated volume that includes dozens of color photographs